Ways of Improving the Results of Treatment for Pulmonary Thromboembolism - M. I. Neimark; A. G. Zaltsman; A. V. Akatov; A. V. Beller; S. V. Zaitsev; M. V. Boyarkov (Общая реаниматология)
Objective: to reveal the predictors of clinically significant deterioration of cardiac pump function resulting from alveolar opening maneuver (AOM) (mobilization) made early after extracorporeal circulation during standard cardiosurgery. Subjects and methods. Hemodynamic, clinical, and laboratory parameters were analyzed in 20 cardiosurgical patients who had undergone AOM in the early postperfusion period. The study inclusion criteria were a PaO2/FiO2 ratio of less than 350 mm Hg, a cardiac index (CI) of more than 2.5 l/min/m2, a dosage of dopamine and/or dobutamine of not more than 10 ^g/kg/min, and standard AOM performance (Pmax, 30—35 cm H2O; end-expiratory pressure (PEEP), 13—15 cm H2O). Regression analysis was used to identify the predictors of a clinically significant reduction in CI (less than 2.5 l/min/m2). Results. Before and after AOM, CI was 3.1±0.1 and 2.9±0.1 l/min/m2, respectively (p>0.05); however, CI was less than 2.5 l/min/m2 (2.16±0.09 l/min/m2) in 25% of cases. After AOM, CI values were significantly related to those recorded prior to a respiratory procedure (p=0.039), total peripheral vascular resistance index (TPVRI) (p=0.00039), and intrapulmonary blood shunt fraction (Qs/Qt) (p=0.041). There were no relationships to other recorded and estimated hemodynamic parameters (p>0.1). – After AOM, CI values were unrelated (p>0.1) to the duration of extracorporeal circulation, the period of myocardial ischemia, and the used dosages of inotropic agents. The predictor of a clinically significant CI reduction after AOM was the only index TPVRI (p=0.00025) recorded before a respiratory procedure. Following AOM, the probability of a significant CI reduction substantially increased (the approximation coefficient R2=0.75) at TPVRI values of 2000 din^sec^cm-5^m2 or more. Conclusion. After AOM performed in the early period after extracorporeal circulation, CI values are related to the baseline level of CI, TPVRI, and Qs/Qt; however, after this procedure only the value of TPVRI is a reliable predictor of clinically significantly depressed cardiac pump function. The risk of persistent car-diodepression is highest at TPVRI values of 2000 din^sec^cm-5^m2 or more. AOM should be carried out early after extra-corporeal circulation in cardiosurgical patients, by making an invasive monitoring that makes it possible to maximally correctly evaluate central hemodynamics, including CI and TPVRI. Key words: alveolar opening maneuver (mobilization), lung recruitment, recruiting maneuver in cardiosurgical patients, central hemodynamics during lung recruitment, cardiodepression during lung recruitment.